2018
DOI: 10.1057/s41271-018-0141-0
|View full text |Cite
|
Sign up to set email alerts
|

Should suicide prevention training be required for mental health practitioners? A Colorado, United States case study

Abstract: Suicide is a critical public health problem, resulting in more than 40,000 deaths a year in the United States (U.S.) and 800,000 globally. Provision of mental health services is a key component of a comprehensive population-based approach to prevention. State licensing boards in some U.S. states require mental health practitioners to be trained in suicide risk assessment and management, but such requirements are not uniform. Our case study examined mental health practitioner preparedness to engage in suicide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Continuing education (CE) credits are another method in which mandatory suicide prevention training has been required at the state level. Schwab-Reese et al (2018) showed that various MHP disciplines used this approach; as of early 2017, most licensing boards in professional counseling, psychology, and social work require CEs for annual licensed renewal. However, CE requirements are not consistent among mental health specialties, with very few requiring suicide prevention as a specific topic.…”
Section: Suicide Prevention As a Required Competency For Mhpsmentioning
confidence: 99%
“…Continuing education (CE) credits are another method in which mandatory suicide prevention training has been required at the state level. Schwab-Reese et al (2018) showed that various MHP disciplines used this approach; as of early 2017, most licensing boards in professional counseling, psychology, and social work require CEs for annual licensed renewal. However, CE requirements are not consistent among mental health specialties, with very few requiring suicide prevention as a specific topic.…”
Section: Suicide Prevention As a Required Competency For Mhpsmentioning
confidence: 99%
“…(1) manage attitudes and reactions to STBs including personal bias, (2) maintain a collaborative and empathetic therapeutic relationship, (3) determine evidence-based risk and protective factors, (4) prioritize imminent suicidal behaviors, (5) assess risk level, ( 6) collaborate with clients on evidence-based treatment, (7) include social support in treatment plan, (8) document treatment decisions, (9) know legal and ethical considerations, and (10) engage in debriefing and self-care (Cramer et al, 2013). The CCM can be applied in an online format (Cramer et al, 2019), a semester-long course (Cramer et al, 2016), and through in-person workshops Hager et al, 2023;La Guardia et al, 2019).…”
Section: Addressing Ethical Considerations Through Suicide Prevention...mentioning
confidence: 99%
“…Most of the 11 states that require training in suicide prevention implemented the requirement through state licensing boards requiring MHPs to complete suicide-specific CE for licensure (AFSP, 2023; Schwab-Reese et al, 2018). With the Matt Adler Suicide Assessment, Treatment, and Management Act of 2012, Washington became the first state to enact legislation to require suicide prevention training (i.e., 6 hr every 6 years) for MHPs (Stuber & Quinnett, 2013).…”
Section: Implementing Mandated Suicide Prevention Trainingmentioning
confidence: 99%